Actividad espacio-temporal de Polietes meridionalis Peris & Llórente , 1963 ( Díptera : Muscidae ) en un ecosistema de encinar * (Boletín de Sanidad Vegetal Plagas, 1995)
Some aspects of the biology of Polietes meridionalis Peris & Llórente 63 have been analysed in a holm-oak ecosystem (dehesa) located in the Tberian Mediterranean área. The specimens were caught with pit-fall traps baited with cattle dung, placed according to habitat gradient. They were collected at dífferent hourly periods to fix a distribution model in space and time and its variation during the year.

Primera cita ibérica de Brachypalpus valgus ( Panzer , 1798 ) y Chrysotoxum parmense Rondani , 1845 ( Diptera : Syrphidae ): caracterización polínica de su dieta * (Boln. Asoc. esp. Ent, 1995)
The first Iberian specimens of the genus Brachypalpus and species Chrysotoxum parmense ha ve been caught in the Font Roja Natural Park (Alicante, Spain). The presence of these two species and the Psilota anthracina, indícales the importance of this Mediterranean holm oak sheltering threatened species in nearby countries like France and Germany. The pollen Lypes found in the alimentary canal of syrphids, are indicated for the first time.